Tertiary syphilis and Kaposi sarcoma mistaken for systemic sarcoidosis in an HIV‐negative patient. (16th October 2015) - Anyasodor, M.C.; Bewley, A.
Summary: We describe a case of an HIV‐negative man who was mistakenly diagnosed as having systemic sarcoidosis, which led to a delay in diagnosing tertiary syphilis and Kaposi sarcoma (KS). The patient presented initially with scrotal swelling and leg oedema. Initial blood tests were unremarkable and HIV testing was negative. The patient then developed unilateral limb weakness. Computed tomography showed lung lesions and hilar lymphadenopathy, while magnetic resonance imaging showed an increased signal in the cervical cord. Serum angiotensin‐converting enzyme was raised, and a diagnosis of sarcoidosis was made and the patient started on steroids. Subsequently, his clinical symptoms and radiological abnormalities improved. However, he then developed progressive neurological deficits over several weeks, together with uveitis and cutaneous lesions. A uveitis screen showed a raised venereal disease research laboratory test titre and the cause of his multisystemic symptoms was revisited. He was diagnosed with tertiary syphilis and treated with antibiotics. Dermatologists reviewed the skin lesions and diagnosed KS, which was confirmed with biopsies. The patient's neurological deficit remains. Syphilis should be considered in the differential diagnosis of any patient presenting with neurological problems, skin lesions or symptoms affecting multiple systems. Co‐existing KS presented an extra therapeutic challenge in this case. Abstract : What's already known about this topic? If left untreated, syphilis infection can progress to involve multiple systems and be easily mistaken for other diseases. What does this study add? This is the first report of both syphilis and Kaposi sarcoma (KS) occurring in an HIV‐negative individual. Treating co‐existent tertiary syphilis and KS presented a therapeutic challenge, as the need to start antibiotics had to be weighed against the need to start immunosuppressive chemotherapy.